Genomic resources for lupins are coming of age. Issue 3 (16th March 2021) - Kamphuis, Lars G.; Garg, Gagan; Foley, Rhonda; Singh, Karam B.
Abstract: Lupins are underutilised pulse crops subject to increasing interest for human consumption of the high‐protein grain. They are also valued as a source of animal nutrition and make an excellent break crop in agricultural production systems. Like other orphan legumes, the genomic revolution has made it cost‐effective to also apply modern genetic and genomic approaches in lupins. These have predominantly been conducted in the two major domesticated lupin species, namely, narrow‐leafed lupin (NLL; Lupinus angustifolius ) and white lupin ( Lupinus albus ), with transcriptome studies also emerging in other domesticated and undomesticated species. This review provides an overview of the current lupin genomic resources developed including two reference genomes for NLL and white lupin, several transcriptome resources and the development of pan‐genomes for NLL and white lupin, and describes how these offer great potential to increase grain yield and quality for these recently domesticated pulse crops. Furthermore, we highlight the importance of lupins to further our understanding of many aspects of fundamental legume biology. Combined, this will aid breeders and growers to improve lupin crops to help meet the increasing demand for plant protein in more sustainable cropping systems.